Anti-tumor Activity of miniPEG-γ-Modified PNAs to Inhibit MicroRNA-210 for Cancer Therapy - Anisha Gupta; Elias Quijano; Yanfeng Liu; Raman Bahal; Susan E. Scanlon; Eric Song; Wei-Che Hsieh; Demetrios E. Braddock; Danith H. Ly; W. Mark Saltzman; Peter M. Glazer (Elsevier, 2017)
MicroRNAs (miRs) are frequently overexpressed in human cancers. In particular, miR-210 is induced in hypoxic cells and acts to orchestrate the adaptation of tumor cells to hypoxia. Silencing oncogenic miRs such as miR-210 may therefore offer a promising approach to anticancer therapy. We have developed a miR-210 inhibition strategy based on a new class of conformationally preorganized antisense γ peptide nucleic acids (γPNAs) that possess vastly superior RNA-binding affinity, improved solubility, and favorable biocompatibility. For cellular delivery, we encapsulated the γPNAs in poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs). Our results show that γPNAs targeting miR-210 cause significant delay in growth of a human tumor xenograft in mice compared to conventional PNAs. Further, histopathological analyses show considerable necrosis, fibrosis, and reduced cell proliferation in γPNA-treated tumors compared to controls. Overall, our work provides a chemical framework for a novel anti-miR therapeutic approach using γPNAs that should facilitate rational design of agents to potently inhibit oncogenic microRNAs.